PENGARUH TAMBANG BATUBARA SEBAGAI PENINGKAT KEHIDUPAN SOSIAL TERHADAP KESEHATAN IBU HAMIL - Rita Kirana (LPSDI Bina Patria, 2023)
Environmental pollution comes from coal mining, causing inorganic materials such as several types of metals, namely mercury, lead (Pb), cadmium (Cd), and arsenic, with relatively small concentrations which can harm living things. This causes communities around coal mines to have a higher probability of being exposed to metals such as Pb and Cd, causing oxidative stress. Oxidative stress can be prevented with antioxidants as a mechanism for the body's defense system against free radicals. This mechanism consists of enzymatic and non-enzymatic. Enzymatic mechanisms include Gluthathione Peroxidase (GSH-Px), Catalase (CAT), and Superoxyde Dismuthase (SOD). The research objective was to determine the effect of coal mining as an enhancer of social life through the difference in average levels of Superoxide Dismutase (SOD) between pregnant women in Ring 1 and 2 of the coal mining area. The research design was cross sectional, observations were made on 9 pregnant women in Ring 1 of the coal mining area and 9 pregnant women in Ring 2 of the coal mining area. Samples were selected by consecutive sampling, examined at the Biomedical and Biochemical Laboratory. SOD levels were examined using the ELISA method. Shapiro-Wilk data normality test was performed, independent T test for different means of normally distributed data. Based on the results of the study, it was found that the average SOD level in pregnant women in Ring 2 of the coal mine was higher (177.096 ± 40.34 ɳ/mL) compared to pregnant women in Ring 1 of the coal mine (169.490 ± 29.81 ɳ/mL) with a p value of 0.513 (p>0.05).